Emergence and Characterization of Serotype G9 Rotavirus Strains from Africa - Page, Nicola; Esona, Mathew; Nyangao, James; Mwenda, Jason; Sebunya, Theresa; Geyer, Annelise; Steele, A. Duncan (Journal of Infectious Diseases, 2010)
Serotype G9 strains have been detected sporadically and in localized outbreaks in various African countries, including South Africa, Botswana, Malawi, Kenya, Cameroon, Nigeria, Ghana, Guinea-Bissau, Libya, and Mauritius. Serotype G9 strains were analyzed to investigate genogroup characteristics, including subgroup specificity, electropherotype, and P and G genotypes. In addition, the antigenic composition of the South African G9 strains was assessed. African G9 strains were associated with both DS-1-like characteristics and Wa-like characteristics, indicating the predisposition of G9 strains to frequently reassort. Despite these reassortment events, serotype G9 strains appear to maintain antigenic character in the outer capsid protein, as evident with the reaction of the South African G9 strains with the G9-specific monoclonal antibody F45:1. Phylogenetic analysis clustered African G9 strains geographically, regardless of genogroup characteristics, into 1 lineage (IIId). Two groups of G9 strains, originating in India and Japan, were identified in this lineage. Continuous surveillance of circulating rotavirus strains in Africa is vital to prepare for future vaccine implementation on a continent that clearly needs such preventative medicines.
Keywords: Serotype G9 Rotavirus Strains; Characterization; Emergence